2021
DOI: 10.1364/oe.419668
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of high-quality orbital angular momentum vortex beams in an adiabatically helical-twisted single-mode fiber

Abstract: A novel method to control the parameters of a chiral fiber grating structure is proposed. Mode couplings are controlled in real time during the twisting fabrication process. This chiral grating structure can satisfy the phase-matching condition for generating high-quality orbital angular momentum (OAM) beams, with an order mode of conversion efficiency over 99.9%. Both theoretical analysis and experimental results of this OAM mode conversion have been investigated, with good agreement. The results demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 48 publications
0
5
0
2
Order By: Relevance
“…1, the CLPG is fabricated by twisting a single-mode fiber (SMF) (Corning, SMF-28e(R)). The fabrication setup consists of three parts: the double-beam CO2 laser heating part, the twisting part, and the online monitoring part 38 . Experimentally, a two-beam CO2 laser is used to heat and soften the fiber due to the advantages of clean, uniform heating, and power stability.…”
Section: Sensor Fabrication Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…1, the CLPG is fabricated by twisting a single-mode fiber (SMF) (Corning, SMF-28e(R)). The fabrication setup consists of three parts: the double-beam CO2 laser heating part, the twisting part, and the online monitoring part 38 . Experimentally, a two-beam CO2 laser is used to heat and soften the fiber due to the advantages of clean, uniform heating, and power stability.…”
Section: Sensor Fabrication Methodsmentioning
confidence: 99%
“…The fabrication setup consists of three parts: the double-beam CO 2 laser heating part, the twisting part, and the online monitoring part. 38 Experimentally, a two-beam CO 2 laser is used to heat and soften the fiber due to the advantages of clean, uniform heating, and power stability. As a result, the resulting fiber gratings have very flat surfaces and lower fiber gratings losses.…”
Section: Fabrication Of High-quality Clpgmentioning
confidence: 99%
See 2 more Smart Citations
“…However, according to the mode coupling theory of CLPG, the effective bandwidth of circularly polarized light generated based on double helix CLPG is only ~10 nm, which greatly limits its application in alloptical communication and sensing systems. In our previous study, we found that the principle of double resonance based on the inflexion of mode dispersion can increase the bandwidth of mode coupling and realize the filtering characteristics of ultra-broadband [5]. Therefore, introducing the dispersion transition characteristic into the double-helix CLPG mode coupling, it is expected to realize the broadband all-fiber circular polarizer.…”
Section: Introductionmentioning
confidence: 99%